The development and implementation of a theory-informed, integrated mother-child intervention in rural Uganda - Singla, Daisy R.; Kumbakumba, Elias (Social Science & Medicine, 2015)
Rationale: A randomised cluster effectiveness trial of a parenting intervention in rural Uganda found benefits to child development among children 12e36 months, relevant parenting practices related to stimulation, hygiene and diet, and prevented the worsening of mothers' depressive symptoms. An examination of underlying implementation processes allows researchers and program developers to determine whether the program was implemented as intended and highlight barriers and facilitators that may influence replication and scale-up. Objectives: The objectives of this study were to describe and critically examine a) perceived barriers and facilitators related to implementation processes of intervention content, training and supervision and delivery from the perspectives of delivery agents and supervisors; b) perceived barriers and facilitators related to enactment of practices from the perspective of intervention mothers participating in the parenting program; and c) whether the program was implemented as intended. Methods: Semi-structured interviews were conducted at midline with peer delivery agents (n ¼ 12) and intervention mothers (n ¼ 31) and at endline with supervisors (n ¼ 4). Content analysis was used to analyze qualitative data in terms of barriers and facilitators of intervention content, training and supervision, delivery and enactment. Additionally, mothers' recall and enactment of practices were coded and analyzed statistically. Monitoring of group sessions and home visits were examined to reveal whether the program was implemented as intended. Results: Among the program's five key messages, ‘love and respect’ targeting maternal psychological well-being was the most practiced by mothers, easiest to implement by delivery agents, and mothers reported the most internal facilitators for this message. A detailed manual and structured monitoring forms were perceived to facilitate training, intervention delivery, and supervision. Interactive and active strategies based on social-cognitive learning theory were reported as facilitators to intervention delivery. Only program attendance, but not barriers, facilitators or message recall, was significantly positively related to message enactment. Monitoring of group sessions and home visits showed that the program was largely implemented as intended. Conclusions: This implementation assessment revealed a number of important barriers and facilitators from the perspectives of delivery agents, supervisors and program participants. The methods and results are useful to examining and informing the content, delivery, and scaling up of the current program as well as future mother-child interventions in LMIC settings.
Keywords: Maternal depressive symptoms; Child development; Parenting; Intervention; Implementation science; Developing countries